Language Interference and Generative Phonology in Speech Production among Hiligaynon Native Speakers - April Jane Sales (REiLA)
Among the places in Negros, Mambukal Resort is one of the spots where the English Language is the only utilised language between foreign tourists and the Hiligaynon vendors. This descriptive-qualitative study investigated the language interferences in speech production among Hiligaynon native speakers who use English as the second language in every transaction in Mambukal Resort, Negros Occidental. This study used the conceptual analysis technique to describe the content of documents found in the data gathered. Using the self-made guide questions for the interview process, the five recorded responses from 5 different representatives of the Flower shops located in this resort were successfully transcribed, analysed and interpreted. This study is anchored on Language Interference and Generative Phonology theory by Noam Chomsky and Morris Halle. With the K-12 program evident in the Philippines, data reveals that 4 out of 5 respondents have graduated at their junior level. Convenient purposive sampling was used in selecting the participants. Findings show that they had difficulty putting correct emphases on the correct syllables, and there is an unprecedented wave of intonation in each word. The pronunciation of the vowel sounds is compromised, and there needs to be more indicative of the content's comprehension. These findings led to the conclusion that respondents' L1 greatly influences not just the adaptation of the suprasegmental features of the target language but also the segmental features. It is recommended that language teachers be fully equipped with the governing standards of the first and second language to impart the use of the right language in the right circumstance. Students must be aware of the unique suprasegmental features of both languages through constant exposure to these languages.